Pilot Study: Prospective, First-in-human Clinical Evaluation of a Novel Tissue Apposition Device (ENIVO) Following Simple Unilateral Mastectomy - Jenny Wagener, MBChB; Usha Shan, MBBS; William F. Anderson, MBChB; Isaac T.T. Mason, BEng; Barnaby C.H. May, PhD; Michelle B. Locke, MBChB (Plastic and Reconstructive Surgery, Global Open)
Background:. Surgery resulting in tissue removal and the formation of dead space is traditionally managed with surgical drains. Drains are used to reduce fluid accumulation and decrease the risk of infection, dehiscence, and seroma formation. However, drains do not actively appose adjacent tissue planes to address dead space. A first-in-human clinical study was undertaken following simple unilateral mastectomy using a novel tissue apposition device. Methods:. This prospective pilot study collected data on 10 participants undergoing simple unilateral mastectomy who would otherwise have received standard surgical drains as part of postoperative management. Participants were instead managed with a pulsed air closure technology (PACT) device designed to remove fluid and to appose adjacent tissue planes of the excisional site. Participants were monitored for complications, fluid output, and fluid accumulation, with a 3-month follow-up. Results:. The mean tissue excised was 793.7 ± 353.9 g. The PACT device removed a mean cumulative fluid volume of 306.2 ± 163.7 mL during a mean treatment duration of 6.5 ± 1.5 days. Ultrasound assessment, at approximately 14 days postoperatively, estimated a median fluid accumulation of 6.9 mL (interquartile range: 0.0–66.2 mL) at the treatment site. Minor complications included exit site bruising, erythema before drainage catheter removal, and a single resolving superficial infection. Only 1 participant developed a seroma requiring clinical intervention. Conclusions:. The PACT device performed its intended function in simple unilateral mastectomies. Minor complications were similar to those observed with traditional surgical drains and all resolved by the 3-month follow-up. These findings warrant further investigation in larger cohorts and in additional surgical applications.